Carbon and nitrogen stable isotope ratios of pelagic zooplankton elucidate ecohydrographic features in the oligotrophic Red Sea. (January 2016) - Kürten, Benjamin; Al-Aidaroos, Ali M.; Kürten, Saskia; El-Sherbiny, Mohsen M.; Devassy, Reny P.; Struck, Ulrich; Zarokanellos, Nikolaos; Jones, Burton H.; Hansen, Thomas; Bruss, Gerd; Sommer, Ulrich
Highlights: The natural ecohydrographic gradient of the Red Sea translates into an isoscape. The Red Sea isoscape features increasing zooplankton δ 15 N values towards the South. Isotopic baseline variations propagate through the pelagic food web. Eddy-induced upwelling modifies the natural ecohydrographic North-South gradient. Abstract: Although zooplankton occupy key roles in aquatic biogeochemical cycles, little is known about the pelagic food web and trophodynamics of zooplankton in the Red Sea. Natural abundance stable isotope analysis (SIA) of carbon ( δ 13 C) and N ( δ 15 N) is one approach to elucidating pelagic food web structures and diet assimilation. Integrating the combined effects of ecological processes and hydrography, ecohydrographic features often translate into geographic patterns in δ 13 C and δ 15 N values at the base of food webs. This is due, for example, to divergent 15 N abundances in source end-members (deep water sources: high δ 15 N, diazotrophs: low δ 15 N). Such patterns in the spatial distributions of stable isotope values were coined isoscapes. Empirical data of atmospheric, oceanographic, and biological processes, which drive the ecohydrographic gradients of the oligotrophic Red Sea, are under-explored and some rather anticipated than proven. Specifically, five processes underpin Red Sea gradients: (a) monsoon-related intrusions of nutrient-rich Indian Ocean water; (b) basin scale thermohaline circulation; (c) mesoscale eddy activity that causes up-welling of deep water nutrients into the upper layer; (d) the biological fixation of atmospheric nitrogen (N2 ) by diazotrophs; and (e) the deposition of dust and aerosol-derived N. This study assessed relationships between environmental samples (nutrients, chlorophyll a ), oceanographic data (temperature, salinity, current velocity [ADCP]), particulate organic matter (POM), and net-phytoplankton, with the δ 13 C and δ 15 N values of zooplankton collected in spring 2012 from 16°28′ to 26°57′N along the central axis of the Red Sea. The δ 15 N of bulk POM and most zooplankton taxa increased from North (Duba) to South (Farasan). The potential contribution of deep water nutrient-fueled phytoplankton, POM, and diazotrophs varied among sites. Estimates suggested higher diazotroph contributions in the North, a greater contribution of POM in the South, and of small phytoplankton in the central Red Sea. Consistent variation across taxonomic and trophic groups at latitudinal scale, corresponding with patterns of nutrient stoichiometry and phytoplankton composition, indicates that the zooplankton ecology in the Red Sea is largely influenced by hydrographic features. It suggests that the primary ecohydrography of the Red Sea is driven not only by the thermohaline circulation, but also by mesoscale activities that transports nutrients to the upper water layers and interact with the general circulation pattern. Ecohydrographic features of the Red Sea, therefore, aid in explaining the observed configuration of its isoscape at the macroecological scale.